2013
DOI: 10.1007/s13205-013-0143-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of plant growth promoting endophytic bacteria from the rhizome of Zingiber officinale

Abstract: Endophytes, by residing within the specific chemical environment of host plants, form unique group of microorganisms. Microbially unexplored medicinal plants can have diverse and potential microbial association. The rhizome of ginger is very remarkable because of its metabolite richness, but the physiological processes in these tissues and the functional role of associated microorganisms remain totally unexplored. Through the current study, the presence of four different endophytic bacterial strains were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 38 publications
5
81
0
2
Order By: Relevance
“…The plant oil from the rhizome extracts has anti-inflammatory and anti-microbial activities (Pongprayoon et al 1997; Bhuiyan et al 2008; Sukatta et al 2009). Recently, several ascomycetous endophytic fungal species were detected in the rhizomes of healthy Zingiber plants (Ginting et al 2013; Jasim et al 2014; Krishnapura and Belur 2016). These results suggest that the number and diversity of endophytic fungi depend on the geographic location rather the host plant species.…”
Section: Resultsmentioning
confidence: 99%
“…The plant oil from the rhizome extracts has anti-inflammatory and anti-microbial activities (Pongprayoon et al 1997; Bhuiyan et al 2008; Sukatta et al 2009). Recently, several ascomycetous endophytic fungal species were detected in the rhizomes of healthy Zingiber plants (Ginting et al 2013; Jasim et al 2014; Krishnapura and Belur 2016). These results suggest that the number and diversity of endophytic fungi depend on the geographic location rather the host plant species.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial genus Staphylococcus, were found previously as endophyte in various agronomic crops (Costa et al, 2012;Jasim et al, 2013); Staphylococcus caprae and Staphylococcus saprophyticus were found as endophyte in Phaseolus vulgaris (Tille, 2017). The genera isolated in the present study that have been previously reported as endophytes are Staphylococcus caprae and Staphylococcus saprophyticus, where Staphylococcus intermedius is found to be new in our research.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that endophytic bacteria produce significant IAA, in B. cereus (Rana et al 2011. ) and P. putida (Jasim et al 2013). The production rate was found to be maximal in the case of P. putida (ECL5) and the minimum in C. michiganensis (ECL6) in the presence of tryptophan.…”
Section: The Isolation Of Endophytic Bacteria From Arachis Hypogaeamentioning
confidence: 95%